PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA KARYAWAN PADA PT. KARET ANDALAS AGROLESTARI KABUPATEN KUANTAN SINGINGI - Rianti, Rasi; ", Kasmirudin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The problem in the research is the indiscipline becomes the factor of decreasing the work performance of employees, where there are still many less appreciate the time such as coming late to the company in accordance with the provisions of the discipline of working time set by the company, late return to work during the day after the end of the break, and employees who goes home before office ends. As a result, the execution of activities may be less productive or become impeded by the time that was previously wasted. Other conditions, found work environment, such as cafeteria facilities that are less comfortable, so some employees choose to enjoy lunch outside the company area. The purpose of the study is to determine the effect of work environment and work discipline on employee performance at PT. Karet Andalas Agrolestari.The method in this research is quantitative descriptive, by using SPSS program to analyze the influence of every work environment variable and work discipline on job performence. In the sampling method used census, which is as much as 40 respondents or all employees at the office of PT. Karet Andalas Agrolestari with data collection techniques through questionnaires. In the sampling method used census, which is as much as 40 respondents or all employees at the office of PT. Karet Andalas Agrolestari with data collection techniques through questionnaires.The result of research using multiple linear regression, correlation coefficient test (R) and coefficient of determination (R2), which can be known work environment have significant effect to employee performance, work discipline has significant effect to employee performance, and work environment and work discipline have significant employee performance.Keywords : Work Environment, Work Discipline, Job Performance